The Capability of Artificial Intelligence in Calculating the Losses of Crime Victims - Putra, Panca Sarjana; Siagian, Fahrizal S (Kosmik Hukum, 2025)
Crime has been a problem that has occurred since human civilisation existed. Criminal offences continue to experience significant developments, and so do the efforts to overcome them. Criminal offences cause victims physical, mental, and/or economic losses. Victims' losses need to be compensated through restitution. With global developments, the potential use of artificial intelligence to calculate restitution should be maximised The issues in this research are as follows: First, what are the judicial provisions regarding artificial intelligence in the criminal justice system in Indonesia? Second, how does the capability of artificial intelligence in calculating the losses of crime victims compare to that in the United States? This research uses normative juridical research method with a literature study. The result of this research is that the juridical provisions of Artificial Intelligence in the criminal justice system in Indonesia are not specifically regulated in Indonesia, but only explained in general in several national laws and regulations. Further studies on the ability of artificial intelligence to calculate the losses of crime victims are necessary to achieve legal certainty. Artificial intelligence aims to optimize the estimation of victims' losses to ensure their rights are properly fulfilled. The comparative study of artificial intelligence’s capability in loss calculation between Indonesia and the United States should be properly implemented in Indonesia’s criminal justice system. Incorporating artificial intelligence in restitution calculations aims to eliminate errors or inaccuracies in determining restitution amounts, an issue that frequently arises.